1972
DOI: 10.1159/000197258
|View full text |Cite
|
Sign up to set email alerts
|

Paneth Cell Secretion

Abstract: The secretion of Paneth cells in the rat has been stimulated by pilocarpine, the small intestinal secretions have been collected and their free amino acid concentrations measured. Comparison with a control group of animals not given pilocarpine showed a statistically significant increase in the free amino acid concentrations. 65Zn has been used to label Paneth cells in experiments which indicate that this increase in luminal amino acid concentrations is the result of the action of pilocarpine on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Also, throughout the length of the small intestine, a steady contribution is made by cells exfoliated from the intestinal mucosa, but in view of the large amounts of endogenous amino acid entering the lumen [20], such cell loss probably plays a small part in homeostasis. The evidence presented here and elsewhere [5], indicates that secretion of amino acids by the Paneth cells plays a significant part in amino acid homeostasis and that this role is of particular importance in the distal jejunum and ileum. It has been shown that the presence of an efficient homeostatic mechanism is essential for the proper absorption and utilisation of amino acids in the diet.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Also, throughout the length of the small intestine, a steady contribution is made by cells exfoliated from the intestinal mucosa, but in view of the large amounts of endogenous amino acid entering the lumen [20], such cell loss probably plays a small part in homeostasis. The evidence presented here and elsewhere [5], indicates that secretion of amino acids by the Paneth cells plays a significant part in amino acid homeostasis and that this role is of particular importance in the distal jejunum and ileum. It has been shown that the presence of an efficient homeostatic mechanism is essential for the proper absorption and utilisation of amino acids in the diet.…”
Section: Discussionsupporting
confidence: 61%
“…It has been shown that a high con centration of amino acids in the foetus at a level 9-14 times that of maternal blood [8]. Although other work [5] indicates that Paneth cells secrete amino acids into the small intestinal lumen, it may also be that the rate of movement of amino acids across the small intestinal mucosa towards the plasma is also variable.…”
Section: Discussionmentioning
confidence: 99%
“…This work agrees with that of N asset [13] who has demonstrated the presence of a free amino acid pool in the small intestine which is sufficiently large, that by mixing with the amino acids from ingested food, can ensure that a mixture of amino acids which is always very similar in composition is available for absorption. Our work on Paneth cell function in the rat [7] indicates that secretion of amino acids by these cells plays a part in the maintenance of this amino acid pool in the small intestine.…”
Section: Amino Acidmentioning
confidence: 83%
“…N asset and Ju [14] have provided much evidence which shows that this movement into the small intestinal lumen may be a substantial one. As a result of our experiments in which Paneth cell secretion in rats was stimulated by pilocarpine [7], our interest in this subject was aroused. The following observations were designed with the purpose of investigating the changes which may occur in solutions of free amino acids at various concentrations when they are instilled into the small intestine.…”
mentioning
confidence: 99%
See 1 more Smart Citation